Neurotrophin-3 Promotes the Neuronal Differentiation of BMSCs and Improves Cognitive Function in a Rat Model of Alzheimer's Disease - Yan, Zhongrui; Shi, Xianjing; Wang, Hui; Si, Cuiping; Liu, Qian; Du, Yifeng (Frontiers in Cellular Neuroscience, 2021)
Transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) has the potential to be developed into an effective treatment for neurodegenerative diseases such as Alzheimer's disease (AD). However, the therapeutic effects of BMSCs are limited by their low neural differentiation rate. We transfected BMSCs with neurotrophin-3 (NT-3), a neurotrophic factor that promotes neuronal differentiation, and investigated the effects of NT-3 gene overexpression on the differentiation of BMSCs into neurons in vitro and in vivo. We further studied the possible molecular mechanisms. We found that overexpression of NT-3 promoted the differentiation of BMSCs into neurons in vitro and in vivo and improved cognitive function in rats with experimental AD. By contrast, silencing NT-3 inhibited the differentiation of BMSCs and decreased cognitive function in rats with AD. The Wnt/β-catenin signaling pathway was involved in the mechanism by which NT-3 gene modification influenced the neuronal differentiation of BMSCs in vitro and in vivo. Our findings support the prospect of using NT-3-transduced BMSCs for the development of novel therapies for AD.